TRANSPORTATION SYSTEMS MODELLING: TRANSPORTATION SYSTEMS MODELLING - Rahnev, Mariyan (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
As it is with every activity, the transport network can be organized in many ways by using different technical means and technologies. Taking certain management decisions is connected with the choice of one of the many possible options for realization of the transportation process. This is done with the help of one or a few indicators which serve as a criterion of efficiency, e.g. exploitation costs, profit, safety, time, etc. The research of the transport objects functioning and the optimization of their parameters is a very complicated task in most of the cases. In such cases the solutions of the problems which concern us are derived by the research and experimentation with a substitute (analogue) of the real object, specially designed for this purpose. This analogue is called a model and the process of its creation is called modelling.